An Energy Expenditure Approach for Estimating Walking Distance. (April 2014) - Hsu, Chaug-Ing; Tsai, Yau-Ching
A walking distance of approximately a quarter mile is normally used as an estimate of willingness to walk when planning a pedestrian-related infrastructure. However, there are variations in walking distance across pedestrian environments, yet there is scant empirical literature on the subject. In this study we propose an energy-based approach to aid the planner in establishing reasonable walking distances while taking into account the effect of pedestrian environment quality. The Pandolf et al model (Pandolf et al, 1977 Journal of Application Physiology 44 577–581) is used to analyze the walking energy expenditure (WEE). The terrain factor is adjusted using the calibrated regression function to fit the urban street space in the experiment. A goodness-of-fit test for the 385 WEEs surveyed suggests a gamma distribution. Using the isoenergy curves, walking distances are shown according to energy level, street type, and gender in order to improve the traditional single measure. The results of this study suggest that, instead of a concentric pattern, the pattern of accessible walking distance around a service facility should be designed based on the service contour lines which take into account the different pedestrian environments.